2021
DOI: 10.3390/ijms22094881
|View full text |Cite
|
Sign up to set email alerts
|

Size-Exclusion Chromatography Separation Reveals That Vesicular and Non-Vesicular Small RNA Profiles Differ in Cell Free Urine

Abstract: Urinary extracellular vesicles (EVs) and their RNA cargo are a novel source of biomarkers for various diseases. We aimed to identify the optimal method for isolating small (<200 nm) EVs from human urine prior to small RNA analysis. EVs from filtered healthy volunteer urine were concentrated using three methods: ultracentrifugation (UC); a precipitation-based kit (PR); and ultrafiltration (UF). EVs were further purified by size-exclusion chromatography (SEC). EV preparations were analysed with transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
(65 reference statements)
3
7
0
Order By: Relevance
“…In our study, NTA measurement showed a clear particle peak at SEC fraction 3, which is consistent with findings when EVs are isolated from other body fluids using the same method (Karttunen et al, 2021). In fraction 3, particles detected by NTA had a modal size of around 100nm, whereas particles measured by NanoFCM had a modal size of around 70nm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, NTA measurement showed a clear particle peak at SEC fraction 3, which is consistent with findings when EVs are isolated from other body fluids using the same method (Karttunen et al, 2021). In fraction 3, particles detected by NTA had a modal size of around 100nm, whereas particles measured by NanoFCM had a modal size of around 70nm.…”
Section: Discussionsupporting
confidence: 92%
“…The selection of isolation method is a balance between EV yield and purity, which poses challenges for EV biomarker discovery; optimising purity is likely to enhance test specificity, whilst optimising EV yield is necessary to maximise test sensitivity. Ultrafiltration combined with size-exclusion chromatography (UF-SEC) outperforms the differential centrifugation method and/or commercial precipitation-based kits for EV isolation from cell culture supernatant, and urine in terms of purity (Allelein et al, 2021; Karttunen et al, 2021; Sidhom et al, 2020). For CSF EVs, UF-SEC has been reported to increase both yield and purity (Thompson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our study targeted miRNAs and mRNAs that were detected in small uEV-enriched samples isolated by ultracentrifugation, or pEV samples isolated with ExoEasy without further steps of purification or enzymatic treatments (RNAse/proteinase). These steps attempt to remove miRNA in other carriers than EV or miRNA associated with the molecular corona on the EV surface [23,27,74,75]. Our detected miRNAs can therefore be located in or on EV or in other small-sized miRNA carriers remaining in the samples, including recently identified supermeres [27,76].…”
Section: Discussionmentioning
confidence: 80%
“…However, so far, the heterogeneity of the uEV pipelines, on top of the heterogeneity of the PCa tumours and study designs, likely explains why the discovered miRNA biomarker candidates differ [8]. For example, heterogeneity of the isolated uEV and copurified non-EV materials from different isolation workflows impact the miRNA results [7,23,24]. As the average sizes, biogenesis routes and cargo of small and large EV differ [22,[25][26][27], targeting small EV for biomarker analysis is one strategy to limit heterogeneity of the EV and dissect exosomal messages.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, buffer was removed from the columns which were then washed with PBS before instilling the resuspended precipitate or ultrafiltered urine, which was then followed by elution with PBS. The first 1000-μL fraction was discarded, and the following 600 μL collected as the EV rich fraction, as previously optimised (Karttunen et al 2021). Final uEV preparations were stored at −80°C until further analysis.…”
Section: Study Design and Inclusion Criteriamentioning
confidence: 99%